Factors affecting urine leak after percutaneous nephrolithotomy: a single centre prospective study - Dineshan K.M, Madhavan N*, Sumit More, Edikkula Varghese, Vaibhav Vishal, Felix S Cardosa (Innovative Journal of Medical and Health Sciences, 2020)
PCNL was first performed in late 1970s and it heralded a breakthrough in the treatment of renal stones.1 Although retrograde intrarenal surgery (RIRS) is widely applied in upper urinary stones, the technique of percutaneous nephrolithotomy (PCNL) is still the treatment of choice for large and complex stones